Dual Cross‐linked Vinyl Vitrimer with Efficient Self‐Catalysis Achieving Triple‐Shape‐Memory Properties. Issue 19 (8th August 2019) - Niu, Xiling; Wang, Fenfen; Kui, Xing; Zhang, Rongchun; Wang, Xiaoliang; Li, Xiaohui; Chen, Tiehong; Sun, Pingchuan; Shi, An‐Chang
Abstract: As an emerging class of dynamic cross‐linked network, vitrimers have attracted much attention due to the combination of mechanical advantages of thermosets and recyclability of thermoplastics at an elevated temperature. In particular, most vitrimers with multi‐shape memory properties usually involve more than one thermal transition or molecular switch, which might pose a challenge for facile sample fabrication and potentially limits their applications. In pursuit of a more universal and simple route, utilizing commercially available and inexpensive reagents to prepare shape‐memory vitrimers with dual cross‐linked network from vinyl monomer‐derived prepolymers is reported here. Copolymerization of desired vinyl monomers gives prepolymers containing carboxyl and zinc carboxylate groups, which are later converted into vitrimers in a single step by post‐curing with diglycidylether of bisphenol A. The Zn 2+ ions can not only act as physical crosslinking points through ionic coordination interactions, thus providing the triple‐shape‐memory properties, but also play the role of catalyst to activate transesterification in the dynamic covalent network. This new self‐catalyzed vitrimer has excellent transesterification efficiency, triple‐shape‐memory properties, and can be sufficiently healed and reprocessed at an elevated temperature. The proposed molecular design of self‐catalyzed materials opens a new avenue toward commercially relevant fabrication of high‐performance vitrimers with multiple shape‐memory properties. Abstract : A dual cross‐linked vinyl vitrimer is prepared from diglycidylether of bisphenol A and vinyl copolymer containing carboxyl and zinc carboxylate side groups. The Zn 2+ ions not only act as physical crosslinking points but also as an effective self‐catalyst of transesterification in the dynamic covalent network. The materials exhibit excellent transesterification efficiency, triple‐shape‐memory properties, and can be sufficiently healed and reprocessed.